Skrining Senyawa Metabolit Sekunder Dan Total Fenol Kopi Robusta (Coffea canephora Pierre Ex a. Froehner) Di Daerah Petungkriyono Pekalongan - Muhammad Walid; Dewanti Novela Putri (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
Coffee is herbs having high economic value which has long been used to drink for a long time in the Pekalongan.Coffee robusta constituting a variety of coffee having distinction from other coffee varieties robusta coffee because quality in stir by means of processing, the climate the planting and growing trees coffee influences the decomposition of a chemical compound which is found in soil and organic influence on the ripening fruit.This report is written with non experimental method, the extraction of coffee beans macerated using ethanol 96 %, a compound of a metabolite secondary identified by test color and chromatography thin layers, the determination of the total phenol done with spektrofotometri UV-Vis and expressed in mg GAE / grams extract.The research results show that robusta coffee beans that grows in Petungkriyono Pekalongan secondary of a metabolite compounds containing an alkaloid, flavonoid, saponin, tannin, triterpenoid, and phenol.Testing to the total phenol which is found in a seed of the coffee robusta obtained a total value of as much as 565,5 GAE / g. Phenol.